2016
DOI: 10.15252/embr.201541763
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA EGOT negatively affects the antiviral response and favors HCV replication

Abstract: The role of long noncoding RNAs (lncRNAs) in viral infection is poorly studied. We have identified hepatitis C virus (HCV)-Stimulated lncRNAs (CSRs) by transcriptome analysis. Interestingly, two of these CSRs (PVT1 and UCA1) play relevant roles in tumorigenesis, providing a novel link between HCV infection and development of liver tumors. Expression of some CSRs seems induced directly by HCV, while others are upregulated by the antiviral response against the virus. In fact, activation of pathogen sensors induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
132
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 71 publications
3
132
2
2
Order By: Relevance
“…lncRNAs have been reported to play important roles in the regulation of the IFN response and ISG induction in HCV infection . For example, the lncRNA EGOT has been shown to increase HCV replication by suppressing the antiviral response through the NF‐κB pathway . HCV infection in turn activates PKR and induces NF‐κB, EGOT, and, subsequently, ISG15 transcription to block the RIG‐I pathway, inhibiting the expression of several ISGs to enhance HCV replication .…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been reported to play important roles in the regulation of the IFN response and ISG induction in HCV infection . For example, the lncRNA EGOT has been shown to increase HCV replication by suppressing the antiviral response through the NF‐κB pathway . HCV infection in turn activates PKR and induces NF‐κB, EGOT, and, subsequently, ISG15 transcription to block the RIG‐I pathway, inhibiting the expression of several ISGs to enhance HCV replication .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the functional roles of EGOT have recently been implicated in ischemic heart diseases (23). Furthermore, another study has found that lncRNA EGOT negatively affects the antiviral response and favors hepatic virus C (HCV) replication (24). These pioneering studies have suggested that EGOT may exert active functional roles in human diseases, including human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the intrinsic pathway may be involved in the apoptosis induction processes induced by EGOT overexpression. However, as a recent report indicated that lncRNA EGOT prefers nuclear localization in HCV-infected cells (24), the subcellular localization of EGOT in human tumor cells remains to be elucidated and merits further investigation into whether the subcellular location is associated with its regulation of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that some lncRNAs could affect virus infection and replication. For example, EGOT affects the antiviral response to HCV, lncRHOXF1 promotes replication of the Sendai virus, and NEAT1 is related to infection with the influenza virus (16)(17)(18). Thus, significant components of HCC treatment are steps to counter the tumor and viruses.…”
Section: Introductionmentioning
confidence: 99%